The current practice of design and build procurement process in Malaysia / Sabihah Saaidin ...[et al.] - Saaidin, Sabihah; Endut, Intan Rohani; Abu Samah, Abu Samah; Mohd Ridzuan, Ahmad Ruslan (UiTM Press, 2016)
This paper discusses the design-build project delivery method which is becoming an increasingly viable alternative to traditional project delivery method in the public sector. This interest has led to dialogue among public sector agencies to establish and formalise understanding of the design-build process and its implementation. The process consists of six stages namely Project Definition, Request for Qualification, Request for Proposal, Proposal Submission and Evaluation, Contract Award, and Document/Construction. Therefore, this finding of Design-Build (DB) procurement process is on the improvement and understanding on an owner and contractor in practice and implementation in Malaysia.